Infecção experimental de coelhos com recombinantes do herpesvírus bovino tipo 5 defectivos nos genes da timidina quinase e da glicoproteína E - Silva, Sara Campos da (2009)
Bovine herpesvirus 5 (BoHV-5) the agent of meningoencephalitis in cattle - is an important pathogen of cattle in South America and efforts have been made to produce safer and more effective vaccines. This dissertation relates an investigation of the virulence in rabbits of three BoHV-5 recombinants, vaccine candidates, defective in the glycoprotein E (BoHV-5gEΔ), thymidine kinase (BoHV-5TKΔ) and both genes (BoHV-5gEΔTKΔ). To this, four groups of eight rabbits each were inoculated intranasally with each recombinant or the parental strain (SV507/99) and monitored thereafter. At day 42 post inoculation (pi) the inoculated animals were submitted to dexamethasone (Dx) administration to reactivate latent infection. At day 70 pi, all animals were euthanized and the brain was collected for investigation of latent viral DNA by PCR. Rabbits inoculated with the parental virus shed virus between days 2 and 8 pi and all rabbits (n=8) developed neurological disease and died or were euthanized in extremis, between days 7 and 13 pi. Among the animals inoculated with the recombinants, viral shedding was detected between days 2 and 10 pi, in 7 out of 8 rabbits of the BoHV-5gEΔ group, in 6 out of 8 rabbits of the BoHV-5TKΔ group and in 3 out of 8 of the BoHV-5gEΔTKΔ group. In spite of variable levels of virus shedding, all rabbits inoculated with the recombinants seroconverted, developing virus-neutralizing antibodies in titers from 2 to 256 at day 42 pi. The rabbits inoculated with the parental virus showed a wide distribution of the virus in their brains, including the olfactory bulbs, cortices, medulla oblongata, pons, midbrain and thalamus. Three out of eight rabbits inoculated with the recombinant BoHV-5gEΔ developed neurological signs at days 10 and 15pi. A more restricted virus distribution, confined mainly to cerebral cortices and thalamus was detected in the brain of these animals. Rabbits inoculated with the recombinants BoHV-5TKΔ (n=8) or BoHV-5gEΔTKΔ (n=8) remained healthy during the experiment. Dx administration to rabbits inoculated with the three recombinants at day 42 pi did not result in viral reactivation, as demonstrated by lack of seroconversion or virus shedding. Nevertheless, viral DNA was detected in the trigeminal ganglia or olfactory bulbs of all these animals at day 28pDx, demonstrating they were latently infected. These results showed that the three recombinants were able to establish latent infection yet they were not easily reactivated by Dx administration. In summary, the recombinants BoHV-5TKΔ and BoHV-5gEΔTKΔ are attenuated for rabbits and constitute potential vaccine candidates.